Vestibular Function Measured Using the Video Head Impulse Test in Congenital Nystagmus and Vertigo: A Case Report - Denia-Lafuente, Antonio; Lombardero, Belén (Frontiers in Neurology, 2021)
In patients with congenital nystagmus (CN), the study of vestibular function is complicated by many factors related to the measurement of the vestibulo-ocular reflex (VOR) by means of caloric testing and the video head impulse test (vHIT), and to date no such studies have successfully employed the vHIT to evaluate vestibular function in these patients. We present a case with CN and vertigo in which peripheral vestibular function was evaluated using the vHIT system, including head impulse testing and the suppression head impulse protocol. We show that it is possible a) to identify lateral VOR changes such as abnormalities resembling those produced by bilateral vestibular lesions, though not necessarily related to the same mechanism; b) to identify peripheral VOR lesions of the vertical semicircular canals (SCC); and c) to document compensation and recovery subsequent to these peripheral lesions during follow-up of patients with CN. vHIT is a useful tool that should be used to study vestibular function in patients with CN and vertigo, which could constitute a new clinical application of this technique.